Alienación parental como violación de derechos humanos de la niñez desde la psicología del desarrollo - Pinzón-Pérez, Carlos Israel (2023)
Parental alienation syndrome has been identified more markedly, since the psychiatrist Richard Gardner (1985), defined it as "a childhood disorder, derived from conflicts between parents, related to the custody of their daughters and sons, the result of a programming induced to girls and boys by the defamation of the alienating parent towards the other”. It can be identified as the rejection of the daughter or son, towards their father or mother, as a form of punishment and revenge exercised by one of those parents against their counterpart, who is generally the one who does not maintain custody and custody; This can be a form of child abuse and therefore violate the human rights of children. Objective: To reflect on parental alienation as a violation of children's human rights from developmental psychology. Results: This phenomenon is contemplated in the Constitutional text of the Convention on the Rights of the Child and the diverse Mexican legislation, particularly what is indicated by the General Law on the Rights of Girls, Boys and Adolescents in its article 23, which protects the right that they have, despite the fact that their families are separated, even due to divorce, to live together and maintain personal relationships and direct contact with their mother and father and their other family, doing it regularly, which is in accordance with with their right to mental development and well-being, despite this, it does not appear in the DSM-5. Conclusion: This syndrome violates human rights, since the exercise of rights in childhood must be guaranteed, an affective, understanding and non-violent environment, taking care of their psychological integrity, eliminating acts that impair their integral development, violate respect, generate violence or rejection of their relationships with their parents and other relatives.